Financial Accountability in the Micro, Small and Medium Enterprises Sector During the Covid-19 Pandemic : Akuntabilitas Keuangan Pada Sektor Usaha Mikro Kecil dan Menengah di Masa Pandemi Covid-19 - Mayang Novita Sari; Sarwenda Biduri; Sigit Hermawan (Academia Open, 2021)
This study aims to find out how financial accountability is in the Micro, Small and Medium Enterprises sector during the Covid-19 Pandemic. This research was conducted on 4 MSMEs located in Wunut village, Porong district, Sidoarjo regency. The four MSMEs that are used as objects in this research are Bags and Wallets MSMEs where each of these MSMEs has produced quite a lot of goods every day. In addition to selling local products that are quite attractive to buy, these MSMEs have also been running their business for a long time. There are even some of these MSMEs which are hereditary. However, MSMEs in Wunut village are run without any accounting activity in it. Some of the MSMEs that have been interviewed by researchers admit that they have not implemented financial accountability in the business they run. This study seeks to understand the form of financial accountability carried out by the MSME sector during the Covid-19 pandemic. This research was conducted using a qualitative method using an interpretive paradigm. The results of research on financial accountability in the MSME sector are mostly not standardized and are in the form of single entry accounting.